Christian perspectives on transforming interreligious encounter essays in honor of Leo D. Lefebure - Phan, Peter C. 1943-; Tran, Anh Q. 1965-; Machado, Felix; Lefebure, Leo D. 1952- (Lanham Lexington Books, 2024)
"This book explores different ways in which Christians can creatively interpret the sacred writings of other religions and shows how the various Christian beliefs can be re-articulated in the light of interreligious dialogue, including revelation, Christ, the Holy Spirit, church and salvation, the ethics of violence, and ecology"--
Ways of encountering the religious other -- The Christian Bible and interreligious relations: a conversation with Leo D. Lefebure / John T. Pawlikowski -- A Christian reading of the Bhagavad Gita: relationship and service with God and with others / Kristin Johnston Largen -- Dorothy Day and Pațācārā: two women and their long loneliness / James L. Fredericks.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Lefebure, Leo D -- 1952-; Bible -- Criticism, interpretation, etc; Christianity and other religions; Religions -- Relations; Religious Pluralism -- Christianity; Christianity and other religions -- Biblical teaching; Religions -- Relations -- Biblical teaching; Religious Pluralism -- Christianity -- Biblical teaching; Aufsatzsammlung; Festschrift